2010
DOI: 10.1128/jb.00431-10
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the Colicin M Catalytic Domain Exported to the Periplasm Is FkpA Independent

Abstract: Colicin M (ColM) is a bactericidal protein that kills sensitive cells by hydrolyzing lipid II, involved in the biosynthesis of cell wall peptidoglycan. It recognizes FhuA on the outer leaflet, and its translocation through the outer membrane depends on the energized Ton complex in the inner membrane. To be active in the periplasm, ColM must be translocated through the outer membrane and then interact with FkpA, a periplasmic protein that exhibits both cis-and trans-peptidylprolyl isomerase (PPiase) and chapero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
(32 reference statements)
0
30
1
Order By: Relevance
“…It has been shown that FkpA is necessary for colicin M toxicity in vivo (32,33) and that its PPIase activity is required for this function (34). It has also been shown that FkpA interacts with high affinity with the passenger domain of the autotransporter EspP (35), and, along with DsbC, FkpA has been implicated in the folding of the nonnative passenger domain of a hybrid autotransporter protein (36).…”
mentioning
confidence: 99%
“…It has been shown that FkpA is necessary for colicin M toxicity in vivo (32,33) and that its PPIase activity is required for this function (34). It has also been shown that FkpA interacts with high affinity with the passenger domain of the autotransporter EspP (35), and, along with DsbC, FkpA has been implicated in the folding of the nonnative passenger domain of a hybrid autotransporter protein (36).…”
mentioning
confidence: 99%
“…Active Site Structure-Extensive site-directed mutagenesis studies identified residues Asp-226, Tyr-228, Asp-229, His-235, and Arg-236 from ColM as extremely important for both in vitro catalytic activity and in vivo cytotoxicity (15,(31)(32)(33). These residues are conserved in PaeM and are concentrated on the protein surface (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of the Catalytic/Killing Domain-Protein dissection experiments showed earlier that it was possible to individually express the C-terminal domain of ColM while maintaining its functionality (15,31). Interestingly, the specific activity of the isolated catalytic domain of ColM was much higher (50-fold) than that of the full-length protein, suggesting that the presence of the N-terminal and central domains involved in receptor binding and import steps interfered with the activity of the C-terminal domain.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence indicate that ColM exerts its toxic activity at the periplasmic face of the membrane: (i) ColM has to enter the cell from the external medium to be active since a ColM-producing cell is protected from the toxin it produces as long as it possesses the dedicated immunity protein (Cmi) or if the import machinery is inactivated [6,13]; (ii) the immunity protein is anchored in the inner membrane via a single transmembrane segment and its main structural body emerges in the periplasmic space, where it neutralizes ColM cytotoxicity by a yet unknown mechanism [14,15]; and (iii) when ColM is fused to the signal sequence of OmpA, it is excreted via the Sec apparatus into the periplasm, where it is toxic for the producer unless the immunity protein is co-expressed [16].…”
Section: Mode Of Action Of Colmmentioning
confidence: 99%